ANALYSIS OF FACTORS AFFECTING THE SATISFACTION AND LOYALTY OF THE USE OF CARGO SERVICES: A CASE STUDY OF PT. BEX - Andika A.; Simanjuntak M.; Kirbrandoko (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
The logistics industry is an important industry that plays an important role for other industries. Business uncertainty currently has an impact on almost all industries. Likewise, the logistics industry has also been explained to experience a decline in sales in almost every year. This study uses the PLS approach to solve research problems. The results of the study show that there are several variables that have an important influence on customer satisfaction and loyalty.